The Role of Organizational Leadership to Improving Effectiveness of Public Administration in The Cirebon City Disdukcapil - Ros Awaliyah Rosadah; Vita Dhameria; Eliyawati Eliyawati; Susi Sugiyarsih (Universitas Negeri Surabaya, 2026)
Objective: This study aims to analyze the influence of organizational leadership on the effectiveness of public administration in the Population and Civil Registration Office (Disdukcapil) of Cirebon City. Method: The population in this study included all employees and leaders of the Cirebon City Disdukcapil, and using the census method, questionnaires were distributed to 28 respondents. Results: The results of simple linear regression analysis show that organizational leadership has a positive and significant effect on public administration effectiveness, as indicated by a regression coefficient value of 0.425 and a significance value of 0.001. The ANOVA test also reinforces this finding with a calculated F value of 12.823 and a significance value of 0.001 (< 0.05). Novelty: These findings indicate that visionary, participatory, and innovative leadership are key factors in improving the performance of responsive and high-quality public services, as well as strengthening public trust in population service institutions in the digital age.